Can You Trust Your Trust Measure? - Chita-Tegmark, Meia.; Law, Theresa.; Rabb, Nicholas.; Scheutz, Matthias. (Tufts University. Tisch Library., 2023)
Keywords: human-robot interaction, human-robot trust, subjective trust, trust measure.; Topic: Computer systems organization / Embedded and cyber-physical systems / Robotics; Topic: Human-centered computing / Human computer interaction (HCI) / Interaction paradigms; ACM Open.